2007
DOI: 10.1021/jp066897p
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Optical, and Magnetic Properties of Co-doped SnO2 Powders Synthesized by the Coprecipitation Technique

Abstract: We have used the coprecipitation technique to synthesize polycrystalline Co-doped SnO 2 diluted magnetic semiconductors with Co concentrations of 0, 0.5, and 2.0%. X-ray diffraction patterns showed for all samples the expected SnO 2 tetragonal structure with no additional peaks corresponding to parasitic phases. Transmission electron microscopy (TEM) did not indicate the presence of magnetic parasitic phases and confirmed that Co ions are uniformly distributed inside the samples. Optical absorption measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
77
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(90 citation statements)
references
References 32 publications
13
77
0
Order By: Relevance
“…The absorption spectrum of the pure and Zn-doped SnO 2 nanoparticles is shown in Fig.6. It is clearly observed that the absorption edge shifts towards the higher wavelength side (red shift) with the increase in dopant concentration, which agrees well with the reported results 19 . Although a quantum confinement could be expected due to the decrease of the particle size upon doping, a small decrease of the absorption edge is observed corresponding to a red-shift, similar to the one observed in Co doped SnO 2 and Co-doped ZnO 20,21 .…”
Section: Optical Studiessupporting
confidence: 92%
“…The absorption spectrum of the pure and Zn-doped SnO 2 nanoparticles is shown in Fig.6. It is clearly observed that the absorption edge shifts towards the higher wavelength side (red shift) with the increase in dopant concentration, which agrees well with the reported results 19 . Although a quantum confinement could be expected due to the decrease of the particle size upon doping, a small decrease of the absorption edge is observed corresponding to a red-shift, similar to the one observed in Co doped SnO 2 and Co-doped ZnO 20,21 .…”
Section: Optical Studiessupporting
confidence: 92%
“…The s-d and p-d exchange interactions can give rise to the decline of the conduction band bottom, leading to the band gap narrowing. 18 Fig . 2(a) and (b) plot the temperature dependence of E cp1 and E cp2 energy for all crystals, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The modes A1g (∼631 cm -1 ) and B2g (∼776 cm -1 ) might be related to the expansion and contraction of the vibrating mode of Sn-O bonds, while the Eg mode may be related to the vibration of oxygen in the oxygen plane. Apart from this, both the as-prepared and annealed samples are found to exhibit two more bonds with less intensity between 304 and 692 cm -1 and may not be assigned to parasitic phases in the SnO2 lattice 17,18 . In addition to these peaks, some extra ones have been observed at 244 and 593 cm -1 and the observation of these new peaks may be explained as follows.…”
Section: Optical Studiesmentioning
confidence: 87%